2010
DOI: 10.1186/1475-925x-9-48
|View full text |Cite
|
Sign up to set email alerts
|

Which is the best method of sterilization of tumour bone for reimplantation? a biomechanical and histopathological study

Abstract: IntroductionSterilization and re-usage of tumour bone for reconstruction after tumour resection is now gaining popularity in the East. This recycle tumour bone needs to be sterilized in order to eradicate the tumour cells before re-implantation for limb salvage procedures. The effect of some of these treatments on the integrity and sterility of the bone after treatment has been published but there has yet been a direct comparison between the various methods of sterilization to determine the one method that giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 31 publications
(27 reference statements)
0
40
0
4
Order By: Relevance
“…Recycling of the resected bone segment is a beneficial alternative method that is more economic than the prosthetic devices, as well as durable and more psychological accepted because of its biological nature, and may be achieved by irradiation, freezing or heating (17)(18)(19). Various methods of sterilization of tumor-bearing bone have been described.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recycling of the resected bone segment is a beneficial alternative method that is more economic than the prosthetic devices, as well as durable and more psychological accepted because of its biological nature, and may be achieved by irradiation, freezing or heating (17)(18)(19). Various methods of sterilization of tumor-bearing bone have been described.…”
Section: Discussionmentioning
confidence: 99%
“…Various methods of sterilization of tumor-bearing bone have been described. Autoclaving and boiling lead to the complete destruction of bone cells, but have the disadvantage of leading to considerable decrease in the biological and biomechanical properties of the graft compared to pasteurization and irradiation, causing severe injury to the collagen matrix and bone proteins (17). Liquid nitrogen as an effective and available cryogenic agent may be used for either tissue preservation or destruction.…”
Section: Discussionmentioning
confidence: 99%
“…2). For the three patients who underwent wide resection and recycled tumor bone implantation, the resected tumor bone was immersed in preheated 10% saline at 65°for 20 minutes after eliminating the tumor tissue [9,38,40]. Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Singh et al [12] evaluated the effect of 4 different sterilization methods on the status of tumour cells in limb salvage surgery for bony sarcomas. Their autoclaving cycle was 135°C for 12-15 min at a pressure of twenty-nine pounds per square inch.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Singh and co-workers [12] compared the effect of autoclaving, irradiation and pasteurisation. They found that there was very little alteration in the mechanical properties after irradiation and pasteurisation as compared to sterilisation by boiling which showed degradation of mechanical properties.…”
Section: Review Of Literaturementioning
confidence: 99%